Arctic dance : the Mardy Murie story - Craighead, Charles; Kreps, Bonnie (Portland, Oregon : Graphic Arts Center Publishing, 2002)
From her first glimpse of Alaska as a young girl, Margaret "Mardy" Murie has a special connection to the Northland. After her Yukon wedding to naturalist Olaus Murie, Mardy joined her husband for years of wilderness adventure, becoming his partner in lifetime of conversation efforts. For more than seventy years, Mardy Murie tirelessly championed the environment. Her work led to the founding of The Wilderness Society and the establishment of the Arctic National Wildlife Refuge. She has been known for years as "the mother of the conversation movementt," and recently received the Presidential Medal of Freedom.
Includes index.
Keywords: Women conservationists -- Biography; Murie, Margaret